The Variety of Teaching Material on Online Learning and Physics Learning Outcomes in Gorontalo District High Schools - Nurmila Nurmila; Masri Kudrat Umar; Tirtawaty Abdjul (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2022)
This study discusses the variety of teaching materials in BOLD learning and physics learning outcomes in high schools, with the aim of knowing what materials are used in BOLD learning and finding out student learning outcomes in BOLD learning. The data analysis used in this research is quantitative descriptive analysis. Descriptive research in this study describes the teaching materials used by teachers in BOLD learning, while quantitative is used to see the learning outcomes of students after using these teaching materials. Based on the results of the research, the teaching materials used in BOLD learning are in the form of electronic modules, textbooks, and PowerPoint slides. Student learning outcomes after using the teaching materials are above the predetermined KKM score. The average student learning outcomes after using online learning teaching materials in four schools are above 70, with one school having an average learning outcome of 83 with good criteria, while three other schools obtain scores of 71, 72, and 73 with sufficient criteria. So, it can be said that the variety of teaching materials used in online learning can improve student learning outcomes.